Evaluation of insert design on the performance of repaired composite-Ti alloy joints. (15th December 2019) - Zhu, Yun-tao; Akkerman, Remko; Xiong, Jun-jiang; Luo, Chu-yang; Du, Yi-sen
Abstract: Two kinds of titanium alloy inserts, namely bushing and embedded conical nut, were designed to repair the bearing damaged zone of screwed single-lap carbon fiber/polyimide composite-TC4 alloy joints, respectively. Quasi-static tensile tests were conducted to determine the effects of such repairs in terms of joint strength and joint stiffness concepts. Based on a simplified bearing model, the deformation mechanisms of titanium inserts influencing the joint performance are further discussed. It is concluded that: 1) the load-displacement curves of screwed joints consist of five characteristic stages; 2) the screw tilt significantly increases the failure load of the screw; 3) the use of an embedded conical nut aggravates the screw tilt, while the use of a bushing reduces the effect of screw tilt by distributing the bearing deformation evenly through the thickness. This difference leads to a different repair effect in terms of joint stiffness.